Walking in a smart city: Investigating the gait stabilization effect for biometric recognition via wearable sensors. (December 2019) - De Marsico, Maria; Mecca, Alessio; Barra, Silvio
Abstract: Technology is expected to enhance life in a Smart City: everything is intelligent, digital, interconnected, and inclusive. In addition, all everyday activities are facilitated. This paper presents a biometric authentication strategy based on gait dynamics. The produced signals are acquired by the common mobile device accelerometers (especially those embedded in smartphones). The user has nothing to do but normally approach a controlled entry: authentication is automatically triggered by ambient elements (beacons). This transparent protocol entails user awareness of the authentication since the user has to install a suitable app, therefore it does not cause any covert privacy violation. In addition, it allows avoiding any explicit, possibly cumbersome authentication procedure. Last but not least, the use of a sensor directly embedded in everyday users' equipment supports an efficient approach without the need for further hardware.